The effect of hydrology on the distribution of ammonia-oxidizing betaproteobacteria in impounded black mangroves (Avicennia germinans) - Laanbroek, Hendrikus J.; Keijzer, Rosalinde M; Verhoeven, Jos T.A.; Whigham, Dennis F (Frontiers in Microbiology, 2012)
The distribution of species of aerobic chemolitho-autotrophic microorganisms such as the ammonia-oxidizing bacteria will be governed by pH, salinity and temperature as well as by the availability of oxygen, ammonia, carbon dioxide and other inorganic elements required for growth. Impounded mangrove forests in the Indian River Lagoon, a coastal estuary on the east coast of Florida, are dominated by mangroves, especially black mangrove (Avicennia germinans), that differ in size and density. In March 2009 the management in one of the impoundments was changed for purpose of insect control, by pumping water from the adjacent estuary. We collected soil samples in three different black mangrove habitats in this and an adjacent impoundment in 2008, 2009 and 2010, always in March, to determine the pre- and post-management effects of summer flooding on the distribution of 16s rRNA genes belonging to ammonia-oxidizing betaproteobacteria (β-AOB). At the level of 95% mutual similarity in the 16s rRNA gene, 11 different Operational Taxonomic Units were identified; the majority related to the lineages Nitrosomonas marina (57% of the total), Nitrosomonas sp. Nm143 (23%) and Nitrosospira cluster 1 (18%). Higher salinities of interstitial water, probably due to severe winter drought, had a significant effect on the composition of the β-AOB in March 2009 compared to March 2008. Nitrosomonas sp. Nm143 was replaced as second important lineage by Nitrosospira cluster 1. Simultaneously with the community change, the level of potential ammonia-oxidizing activities decreased by an average of 67%. Long-term summer flooding in 2009 reduced the percentage of N. marina by half in favor of the two other major lineages, but decreased again the potential ammonia-oxidizing activities by 41% on average. No significant differences were observed between the flooded and non-flooded impoundment. There were differences in the community composition of the bacteria in the three black mangrove habitats. N.